Missed opportunities: a cultural-historical activity theory study of the use of authentic literature as a tool for dialogic pedagogy - Roberts, Katy (School of Education, 2026)
This study examines the opportunities for dialogic pedagogy created using authentic literature within the South African primary school classroom. Dialogic pedagogy has been found to be a useful method for provoking higher order thinking (Alexander, 2020). Moreover, authentic literature is considered a powerful tool for engaging learners in dialogue (Miller, 2003). As indicated by the low scores of South African learners in international benchmarking assessments (Roux et al., 2021), the problem which this study sought to address is the lack of a pedagogy that provokes dialogue that leads to further cognitive development. It sought to address this by examining the use of authentic literature as a means of creating dialogue that reveals sophisticated thought. Previous research on the use of authentic literature for the provocation of dialogic pedagogy and the development of cognitive abilities has not been conducted in South Africa. This qualitative study therefore sought to address this gap in the literature by conducting semistructured interviews with three primary school teachers and observing three lessons where authentic literature was used as a pedagogical tool. The data collection took place over the course of a week at an independent primary school in Cape Town, South Africa. Using a Cultural-Historical Activity Theory (CHAT) framework and the Cam-UNAM scheme for educational dialogue analysis (Hennessy et al., 2020), the teachers' objects and actions were analysed to uncover the reasons why dialogic opportunities might be missed. The study determined that authentic literature provokes rich opportunities for dialogue. Teachers' aims of covering the curriculum and testing recall, however, encumbered learner dialogue and further psychological development. These concerns were evident in the way the teachers frequently missed opportunities for dialogue and engagement.